Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kinerja Pegawai di Sekretariat DPRD Provinsi Sumatera Barat - Refni Yulia Reza; Maizul Rahmizal (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
The Provincial Regional People's Legislative Council (DPRD) is a regional people's representative institution that is domiciled as the administrative factor for provincial regional administration. The provincial DPRD consists of members of political parties participating in universal elections who are selected through universal elections. The purpose of this study was to examine the effect of competence and work environment variables on employee performance at the DPRD Secretariat of West Sumatra Province. Collecting data by distributing questionnaires to 94 respondents using a saturated sampling technique, where all members of the population are sampled, using data processing techniques for validity testing, reliability testing, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression testing and test t with the help of the SPSS application. The results of the study show that competence has a positive and significant effect on employee performance at the DPRD Secretariat of West Sumatra Province, and the work environment has a positive and significant effect on employee performance at the DPRD Secretariat of West Sumatra Province.